2004
DOI: 10.1103/physrevlett.93.035504
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of Shells

Abstract: We present a theoretical and experimental study of the fragmentation of closed thin shells made of a disordered brittle material. Experiments were performed on brown and white hen egg shells under two different loading conditions: impact with a hard wall and explosion by a combustible mixture. Both give rise to power law fragment size distributions. A three-dimensional discrete element model of shells is worked out. Based on simulations of the model, we give evidence that power law fragment mass distributions … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
87
2
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(104 citation statements)
references
References 21 publications
6
87
2
5
Order By: Relevance
“…Several possible mechanisms have been put forward to understand the emergence of the universal power law behavior. For rapid break-up of heterogeneous bulk solids with a high degree of brittleness, the self-similar branching-merging scenario of propagating unstable cracks governed by tensile stresses can explain the main features of the fragment mass distribution [5,[11][12][13], while for shell systems an additional sequential binary breakup mechanism has to be taken into account [7,8]. It is an important question of broad scientific and technological interest how plasticity, and the emergence of complicated stress states like shear affect the fragmentation process.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Several possible mechanisms have been put forward to understand the emergence of the universal power law behavior. For rapid break-up of heterogeneous bulk solids with a high degree of brittleness, the self-similar branching-merging scenario of propagating unstable cracks governed by tensile stresses can explain the main features of the fragment mass distribution [5,[11][12][13], while for shell systems an additional sequential binary breakup mechanism has to be taken into account [7,8]. It is an important question of broad scientific and technological interest how plasticity, and the emergence of complicated stress states like shear affect the fragmentation process.…”
mentioning
confidence: 99%
“…In the data analysis, 99 − 99.5% of the total mass of the samples was recovered. In order to evaluate the mass distribution of the fragments, we scanned the pieces with an open scanner obtaining digital images where fragments appear as white spots on the black background [7,8]. This way the identification of fragments is reduced to cluster searching of white pixels.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…During the past decades research on fragmentation mainly focused on the statistics of fragment masses (sizes) obtained by the breakup of heterogeneous materials [1,9,10]. A large number of experimental [1,[5][6][7][8][9][10][11][12][13][14][15][16][17] and theoretical studies [13,[18][19][20][21][22][23][24] have confirmed that the mass distribution of fragments is described by a power law functional form. The exponent of the distribution was found to show a high degree of robustness, i.e., investigations revealed that the value of the exponent does not depend on the type of materials, amount of input energy, and on the way the energy is imparted to the system until materials of a high degree of heterogeneity are fragmented [1,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The value of the exponent is mainly determined by the dimensionality of the system [13,15,18,19,21,23,[25][26][27] and by the brittle or ductile mechanical response of the material [28]. The universality of fragmenting has been shown to be the fingerprint of an underlying phase transition from the damaged to the fragmented phase of the breakup process [5,6,14,18].…”
Section: Introductionmentioning
confidence: 99%